Evaluating Cues for Resuming Interrupted Programming Tasks - DeLIne, Robert; Parnin, Chris (CHI '10: Proceedings of the 28th international conference on Human factors in computing systems, 2010)
Developers, like all modern knowledge workers, are frequently interrupted and blocked in their tasks. In this paper we present a contextual inquiry into developers’ current strategies for resuming interrupted tasks and investigate the effect of automated cues on improving task resumption. We surveyed 371 programmers on the nature of their tasks, interruptions, task suspension and resumption strategies and found that they rely heavily on note-taking across several types of media. We then ran a controlled lab study to compare the effects of two different automated cues to note taking when resuming interrupted programming tasks. The two cues differed in (1) whether activities were summarized in aggregate or presented chronologically and (2) whether activities were presented as program symbols or as code snippets. Both cues performed well: developers using either cue completed their tasks with twice the success rate as those using note-taking alone. Despite the similar performance of the cues, developers strongly preferred the cue that presents activities chronologically as code snippets.
Honorable Mention Best Paper Award